2014
DOI: 10.1371/journal.pone.0113511
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Loss, Not Fragmentation, Drives Occurrence Patterns of Canada Lynx at the Southern Range Periphery

Abstract: Peripheral populations often experience more extreme environmental conditions than those in the centre of a species' range. Such extreme conditions include habitat loss, defined as a reduction in the amount of suitable habitat, as well as habitat fragmentation, which involves the breaking apart of habitat independent of habitat loss. The ‘threshold hypothesis’ predicts that organisms will be more affected by habitat fragmentation when the amount of habitat on the landscape is scarce (i.e., less than 30%) than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 52 publications
2
5
0
Order By: Relevance
“…A7) in Canada lynx's current range is likely to have negative implications for the species (Hoving et al 2005). Consequentially, the ARH of Canada lynx was predicted to decrease by 21-81% in 2030 from the spatial-only perspective, in agreement with other studies documenting the declining trend of available habitat for Canada lynx in this region (Hornseth et al 2014). Yet, the spatio-temporal connectivity estimation indicated that the decline in connectivity might not be so dramatic, due to the stepping-stone effects enhanced by spatio-temporal connectivity.…”
Section: Importance Of the Spatio-temporal Connectivity Given Differesupporting
confidence: 86%
“…A7) in Canada lynx's current range is likely to have negative implications for the species (Hoving et al 2005). Consequentially, the ARH of Canada lynx was predicted to decrease by 21-81% in 2030 from the spatial-only perspective, in agreement with other studies documenting the declining trend of available habitat for Canada lynx in this region (Hornseth et al 2014). Yet, the spatio-temporal connectivity estimation indicated that the decline in connectivity might not be so dramatic, due to the stepping-stone effects enhanced by spatio-temporal connectivity.…”
Section: Importance Of the Spatio-temporal Connectivity Given Differesupporting
confidence: 86%
“…The finding that lynx are able to use areas of new burns offers hope to lynx in increasingly burned landscapes and corroborates a recent study that indicates lynx occupancy is affected by habitat loss but not by habitat fragmentation on a landscape scale (Hornseth et al., ). These authors suggest that in central Ontario, lynx adapted their habitat selection patterns so that fragmentation of quality lynx habitat did not affect lynx occurrence; lynx were able to adapt to local habitat conditions and use small patches of resources, thus surviving in fragmented landscapes (Hornseth et al., ). However, a tipping point must exist in burned landscapes past which the amount of useable fire residuals does not compensate for the amount of habitat lost to new, high‐intensity burned areas and lynx populations suffer.…”
Section: Discussionsupporting
confidence: 85%
“…Utilizing the additional level of data to create an index was deemed superior to losing detail by modeling presence–absence at the transect level (e.g., Hornseth et al. ). We also deemed it superior to model‐based corrections for detectability, such as in occupancy modeling (e.g., Whittington et al.…”
Section: Discussionmentioning
confidence: 99%